Karakteristik pasien dengan infeksi Burkholderia cepacia di RSUP Sanglah pada tahun 2014-2016 - Dea Antariksa; Ni Nyoman Sri Budayanti; Ni Nengah Dwi Fatmawati (Intisari Sains Medis, 2019)
Background: Burkholderia cepacia complex (Bcc) is a group of 17 species that are genetically and phenotypically similiar. Bcc is an opportunistic pathogen in which it will cause an infection in a person who has had a previous severe lung infection or a person with a weak immune system. Objective: This study aims to determine the characteristics of Burkholderia cepacia compleks patients at RSUP Sanglah Denpasar period 2014-2016 Sanglah Hospital. Methods: This was an observational descriptive study with a cross-sectional study design and a retrospective approach. The subjects were 29 patients diagnosed with Burkholderia Cepacia bacteria and performed bacterial culture at Sanglah Hospital on January 1, 2014 s.d. December 31, 2016. The research data is secondary data obtained from the book Microbiology section Sanglah Hospital. Results: The results showed that patients with isolated Burkholderia cepacia who were admitted to Sanglah Hospital consisted mostly of 37.9% old age categories (> 50 years) and adults (18-50 years); 65.5% male sex and 34.5% female gender; 62.1% were admitted to the ICU; 24.1% were diagnosed with sepsis;